2017
DOI: 10.1371/journal.pone.0179950
|View full text |Cite
|
Sign up to set email alerts
|

Targeting breast cancer cells by MRS1477, a positive allosteric modulator of TRPV1 channels

Abstract: There is convincing epidemiological and experimental evidence that capsaicin, a potent natural transient receptor potential cation channel vanilloid member 1 (TRPV1) agonist, has anticancer activity. However, capsaicin cannot be given systemically in large doses, because of its induction of acute pain and neurological inflammation. MRS1477, a dihydropyridine derivative acts as a positive allosteric modulator of TRPV1, if added together with capsaicin, but is ineffective, if given alone. Addition of MRS1477 evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…The compound MRS1477 (Fig. 7F), a positive allosteric modulator of TRPV1, was found to be very robust in inducing apoptosis in human breast cancer cells in vitro and in athymic mouse model (Naziro glu et al, 2017). The growth-inhibitory effects of MRS1477 were observed at fivefold lower concentration relative to capsaicin.…”
Section: Antineoplastic Activity Of Synthetic Capsaicin Analogsmentioning
confidence: 97%
See 1 more Smart Citation
“…The compound MRS1477 (Fig. 7F), a positive allosteric modulator of TRPV1, was found to be very robust in inducing apoptosis in human breast cancer cells in vitro and in athymic mouse model (Naziro glu et al, 2017). The growth-inhibitory effects of MRS1477 were observed at fivefold lower concentration relative to capsaicin.…”
Section: Antineoplastic Activity Of Synthetic Capsaicin Analogsmentioning
confidence: 97%
“…The growth-inhibitory effects of MRS1477 were observed at fivefold lower concentration relative to capsaicin. The proapoptotic activity of MRS1477 was mediated by the TRPV1 receptor (Naziro glu et al, 2017).…”
Section: Antineoplastic Activity Of Synthetic Capsaicin Analogsmentioning
confidence: 97%
“…The effects are TRPV1 specific, since CPZ inhibits both the effect of CPS and MRS1477. However, the tumor growth in MCF-7 tumor-bearing immunodeficient mice is not inhibited by MRS1477, suggesting that in vivo further studies are required [72].…”
Section: Trpv Channels In Cancer Therapymentioning
confidence: 99%
“…TRPV6 had a high level of expression in breast adenocarcinoma tissue [87]. TRPV1 is functionally expressed in SUM149PT breast cancer cells, a model for a very aggressive form of breast cancer (i.e., triplenegative breast cancer) [88], and in MCF7 breast cancer cells [89,90].…”
Section: Transient Receptor Potential Channels In Breast Cancermentioning
confidence: 99%
“…To date, capsaicin inhibits cancer growth in SUM149PT breast cancer cells, by triggering apoptotic/necrotic mechanisms, while capsazepine diminishes these effects [88]. MRS1477, a positive allosteric modulator of TRPV1, when co-applied with capsaicin, diminished the fraction of MCF7 breast cancer apoptotic cells but was ineffective against tumor growth in MCF7 tumor-bearing immunodeficient mice [89]. Another study demonstrated that doxorubicin and melatonin exert synergistic effects against apoptosis and mitochondrial oxidative stress in MCF-7 breast cancer cells by activating TRPV1 [126].…”
Section: Trp Channels As Pharmacological Targets In Breast Cancermentioning
confidence: 99%